The effect of waste cooking oil in warm mix asphalt - Nurul Izzatul Alia, Nazri (2019)
There are many studies have been done to determine the waste material that can be used to improve resistance to rutting, permanent deformation and fatigue cracking due to binder hardening and improve adhesion of binder to aggregate. In this study, the performance of Waste Cooking Oil (WCO) as a bitumen modifier in asphalt concrete pavement was investigated. This study focuses on the addition of WCO in following order 0% as control, 3%, 4%, and 5% by the weight of bitumen. The aim of this study is to investigate the effect of WCO on the engineering properties of Asphaltic Concrete 14. The different percentage of WCO was blended into the bitumen using a high shear mixer at a constant speed of 1000 rpm for one hour at 140℃. Marshall Stability test was carried out to determine the optimum bitumen content of the mixture. The performance of the samples was evaluated through the stability and volumetric properties, resilient modulus and dynamic creep.